THE EFFECT OF OIL REVENUES AND MONETARY STABILITY AGAINST MANUFACTURING SECTOR AND EXCHANGE RATES IN INDONESIA - Zulkifli Zulkifli; Idris Idris; Hasdi Aimon (Program Studi Magister Ilmu Ekonomi, 2014)
This article focused on analyze (1) the effect of oil production, fuel consumption, oil prices, exports and imports of oil and the rate of inflation affects income in the Indonesian manufacturing sector, (2) the effect of manufacturing revenues, the money supply, rate interest, rate of inflation, exports and imports of oil and oil prices affect the rupiah. This research is descriptive and associative. While this type of data is the documentary data, the data source is a secondary data as well as data in the form of time series of quarter one 2000 to quarter four of 2012. This study uses a simultaneous equation model analysis tools in the form of least squares (LS). Endogenous variables in this study the manufacturing sector revenues and the rupiah whereas exogenous variable is oil production, fuel consumption, oil prices, oil exports, oil imports, inflation rates, interest rates and the money supply The study concluded that ( 1 ) the production of crude oil , oil exports and inflation rate is statistically significant and negative to earnings in the Indonesian manufacturing sector , fuel consumption and oil imports significant and positive impact on revenues statistically processing industry in Indonesia , whereas no significant effect on the price of oil and has a statistically positive direction to the manufacturing sector revenues in Indonesia . ( 2 ) the export of oil and oil prices and the negative effect is statistically significant against the rupiah . But the money supply effect is statistically significant and positive against the rupiah , oil imports , interest rates and income do not affect the manufacturing sector is statistically significant and negative against the rupiah , while the inflation rate has no effect is statistically significant and positive exchange Rupiah . Based on the results of these studies can be recommended policies include the government should reduce the consumption of fossil fuels by finding new alternative energy. Although this policy is not popular but the government must revoke the fuel subsidy, in addition to reducing the burden on the state will also have an impact on the reduction of congestion and air pollution. Indonesian government through the banks should maintain exchange rate stability, as the rupiah will reflect the state of the domestic economy. Keywords : manufacturing revenue, exchange rate